Microarray Profiling of Differentially Expressed Genes in Coronary Artery Bypass Grafts of High-Risk Patients with Postoperative Cognitive Dysfunctions - Noor Anisah Abu Yazit; Norsham Juliana; Suhaini Kadiman; Kamilah Muhammad Hafidz; Nur Islami Mohd Fahmi Teng; Nazefah Abdul Hamid; Nadia Effendy; Sahar Azmani; Izuddin Fahmy Abu; Nur Adilah Shuhada Abd Aziz; Srijit Das (MDPI, 2024)
Indexed by WOS/Scopus/ERA